Fat-Free Mass and the Balance Error Scoring System Predict an Appropriate Maximal Load in the Unilateral Farmer's Walk - Michael E. Holmstrup; Michael A. Kelley; Kyla R. Calhoun; Caleb L. Kiess (MDPI AG, 2018)
This study quantified and compared unilateral farmer’s walk (UFW) performance in recreationally active males and females, and determined if additional variables allowed for the prediction of a maximal safe load. Anthropometric (height, body weight (BW), body mass index, body fat percentage, fat-free mass (FFM), and fat mass), muscular endurance (maximal duration side bridge), and balance (Balance Error Scoring System (BESS)) tests were completed. Participants performed a series of 20 s UFW trials (non-dominant side) at a cadence of 66 beats/min. The initial load was 10% of BW and increased by 10% per trial until deviations in spinal alignment or compromised gait patterns were noted, and the series was terminated. The highest load carried before technical failure was recorded. Descriptive and comparative statistics and a stepwise linear regression analysis were utilized to determine relationships between UFW performance and anthropometric, muscular endurance, and balance tests. Males (N = 25) were significantly taller (177.3 ± 6.7 vs. 164.7 ± 7.2 cm, p < 0.05), heavier (81.7 ± 7.0 vs. 62.0 ± 9.4 kg, p < 0.05), and leaner (14.4 ± 4.4 vs. 22.4 ± 4.8%, p < 0.05) than females (N = 26). Further, males had a higher amount of FFM (p < 0.05) than females. The males (52.2 ± 9.0, 64% BW) carried a higher average UFW load than the females (32.5 ± 7.1 kg, 53% BW, p < 0.05). FFM was strongly predictive of UFW load (load = −9.88876 + 0.88679 × (FFM); r2 = 0.774, p < 0.0001). The addition of the BESS test further increased the accuracy of the prediction equation (r2 = 0.800, p < 0.0001). There are differences in UFW performance ability between males and females. As our method does not account for all potential confounding variables, the use of these equations should be combined with technique analysis and participant feedback to ensure an appropriate workload.